Pemanfaatan Platform Digital di SD INPRES RSS OESAPA Kota Kupang dalam Peningkatan Literasi Digital - Kurniawan, Budi; Meilani, Dian; Letasado, Muhamad Rusadi; Bacotang, Bacotang; Nuriyah, Nuriyah (Penerbit Widina, Widina Media Utama, 2025)
The rapid development of digital technology has significantly transformed the field of education; however, its implementation in elementary schools in Kupang City remains limited, as many teachers are unable to optimize digital platforms in classroom learning. This community engagement study aims to enhance teachers’ digital literacy and skills in using interactive digital learning media. A descriptive qualitative approach was employed through training sessions, observations, interviews, and direct mentoring for elementary school teachers, with data analysis conducted using the interactive Miles Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that practice-based training effectively improved teachers’ understanding, skills, and confidence in using digital media such as Wordwall, Bamboozle, and Puzzle.org, while also fostering positive changes in teaching attitudes and creativity. Teachers began integrating digital tools into their lesson plans and demonstrated greater readiness to implement technology-supported learning. These findings suggest that participatory training approaches are effective in cultivating a digital culture within elementary school environments. In conclusion, strengthening teachers’ digital competencies can be achieved through intensive and continuous mentoring; however, sustained support from local government and educational institutions is essential to expand the impact of this program to other regions in East Nusa Tenggara;ABSTRAKPerkembangan teknologi digital telah mendorong transformasi signifikan dalam dunia pendidikan, namun pemanfaatannya pada jenjang Sekolah Dasar di Kota Kupang masih rendah karena banyak guru belum mampu mengoptimalkan platform digital dalam pembelajaran. Penelitian pengabdian masyarakat ini bertujuan meningkatkan literasi digital serta keterampilan guru dalam menggunakan media pembelajaran digital interaktif. Pendekatan kualitatif deskriptif diterapkan melalui pelatihan, observasi, wawancara, dan pendampingan langsung kepada guru-guru SD, dengan analisis data menggunakan model interaktif Miles Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil menunjukkan bahwa pelatihan berbasis praktik langsung meningkatkan pemahaman, keterampilan, dan kepercayaan diri guru dalam mengoperasikan media digital seperti Wordwall, Baamboozzle, dan Puzzle.org, serta memengaruhi perubahan sikap dan kreativitas dalam mengajar. Guru mulai mengintegrasikan teknologi ke dalam Rencana Pelaksanaan Pembelajaran dan menunjukkan kesiapan yang lebih baik dalam menerapkan pembelajaran digital. Temuan ini mengindikasikan bahwa pendekatan pelatihan partisipatif efektif dalam membangun budaya digital di sekolah dasar. Kesimpulannya, peningkatan kompetensi digital guru dapat tercapai melalui pendampingan yang intensif dan berkelanjutan, namun keberlanjutan program membutuhkan dukungan pemerintah daerah dan lembaga pendidikan agar dampaknya dapat diperluas ke wilayah lain di Nusa Tenggara Timur.